Effect of Chlortetracycline Additive in Broilers Fed Local Diets on Antibody Titers to NDV Vaccine - Murwani, Retno; Murtin, Sri (International Journal of Poultry Science, 2009)
A research was carried out to study the effect of antibiotic chlortetracycline in drinking water on broilers antibody titers to NDV vaccine. Broilers were fed local diet with two different sources of essential amino acid i.e. yeast (in diet 1) or mix lysine, methionine and choline (in diet 2). Two hundred and fifty day old chicks CP 707 were randomly assigned into five treatment diets i.e. 1) commercial diet (Dc), 2) diet 1 without chlortetracycline (D1), (3) diet 2 without chlortetracycline (D2), (4) diet 1 plus chlortetracycline 500 ppm via drinking water (D1+), (5) diet 2 plus chlortetracycline 500ppm via drinking water (D2+). Isoenergy diet and water were given ad libitum. NDV vaccine were given simultaneously via eyedrop and subcutaneous on day 4. Serum antibody titers were measured on day 18, 21 and 25 by Haemaglutination Inhibition Test and expressed as Geometric Mean Titer (log 2). Antibody titer to NDV vaccine was already detectable two weeks after vaccination (on day 18). The titer value was highest in D1+ reaching 6.0 which was above protective level and the lowest value was found in D1 i.e. 2.75 (p<0.05). On day 21 the highest titer was also found in D1+ which remained protective i.e. 5.5 and the lowest one in Dc. On day 25 the highest titer was found in D2 (6.5) and the lowest in Dc (4.25) (p<0.05). These results showed that antibody titers to NDV vaccine in broilers receiving local diet minus antibiotics can match the titers of broilers receiving local diet plus antibiotics. Moreover the broilers receiving local diet without antibiotics produced protective and better titers values at the end of sampling period on day 25 or 3 weeks after vaccination, reaching 5.0 in D1 and 6.5 in D2 respectively.